Acute toxicity of birch tar oil on aquatic organisms - Hagner, Marleena; Penttinen, Olli-Pekka; Pasanen, Tiina; Tiilikkala, Kari; Setälä, Heikki (MTT Agrifood Research Finland, 2010)
Koivuöljytisle (birch tar oil; BTO) on grillihiilen valmistuksessa syntyvä sivutuote, joka uusimpien tutkimustulosten mukaan soveltuu kasvinsuojeluaineeksi ja biosidiksi. Tisleellä voidaan torjua rikkakasveja, hyönteisiä sekä kasvitauteja ja sitä voidaan käyttää myös tuholaisten karkotusaineena. Koivuöljytisleen kaupallistaminen kasvinsuojeluaineeksi edellyttää tehojen lisäksi myös sen rekisteröintiä kasvinsuojeluaineeksi ja siten tarkkaa tietoa mahdollisista ympäristövaikutuksista. Tässä tutkimuksissa testattiin tisleen akuuttia myrkyllisyyttä (EC50) vesieliöille, joita käytetään yleisesti ekologisissa toksisuustesteissä. Tulokset osoittivat, että eri eliöiden herkkyys tisleen vaikutuksille vaihtelee: herkin oli Vibrio fisheri bakteeri. Seuraavaksi herkimpiä olivat herkkyysjärjestyksessä Daphnia magna (vesikirppu) < Lumbriculus variegates (liero) < Lemna minor (vesikasvi) < Danio rerio (kala) < Asellus aguaticus (vesisiira) < Lymnaea sp. (vesikotilo).

Birch tar oil (BTO) is a by-product of processing birch wood in a pyrolysis system. Accumulating evidence suggests the suitability of BTO as a biocide or repellent in terrestrial environments for the control of weeds, insects, molluscs and rodents. Once applied as biocide, BTO may end up, either through run-off or leaching, in aquatic systems and may have adverse effects on non-target organisms. As very little is known about the toxicity of BTO to aquatic organisms, the present study investigated acute toxicity (LC50/EC50) of BTO for eight aquatic organisms. Bioassays with the Asellus aquaticus (crustacean), Lumbriculus variegatus (oligochaeta worm), Daphnia magna (crustacean), Lymnea sp. (mollusc), Lemna minor (vascular plant), Danio rerio (fish), Scenedesmus gracilis (algae), and Vibrio fischeri (bacterium) were performed according to ISO, OECD or USEPA-guidelines. The results indicated that BTO was practically nontoxic to most aquatic organisms as the median effective BTO concentrations against most organisms were >150 mg L-1. In conclusion, our toxicity tests showed that aquatic organisms are to some extent, invariably sensitive to birch tar oil, but suggest that BTO does not pose a severe hazard to aquatic biota. We deduce that, unless BTOs are not applied in the immediate vicinity of water bodies, no special precaution is required.
Keywords: Ka; Ta; koivutisle; biosidit; EC50; acute toxicity test; aquatic organisms; birch tar oil; biocide; EC50